Pathology of proventricular tetrameriasis in a free-range chicken - Sewoyo, Palagan Senopati; Putra, I Putu Cahyadi; Nainggolan, Willy Morris (ARSHI Veterinary Letters, 2024)
This case report aimed to investigate the aetiology of proventricular lesions and associated clinical symptoms in local free-range chickens suspected of having proventricular tetrameriasis. Proventricular tetrameriasis is a poultry disease caused by the nematode Tetrameres sp. In this case, 15 local free-range chickens, approximately eight months old, from Gianyar, Bali, Indonesia, exhibited symptoms of anorexia and greenish diarrhoea, resulting in the death of three chickens. One of the deceased chickens underwent thorough examinations, including anatomical pathology (PA), histopathology (HP), hemagglutinin (HA), and hemagglutinin inhibition (HI) tests for Newcastle disease virus (NDV). PA examination revealed blackish and reddish nodules on the proventriculus surface, although both HA and HI tests for NDV returned negative results. HP examination of the proventriculus tissue revealed cross-sections of Tetrameres sp. nematodes with pseudo-coeloms filled with bright eosinophilic fluids. Additionally, ectasia of the proventricular glands, with compression atrophy and mild inflammation, was observed.